A Proposal for Reinforcement of Historical Masonry Minarets: Gaziantep Kabasakal Mosque Minaret - İrfan Kocaman; Merve Ertosun Yıldız; Mehmet Akif Yıldız; Esma Eroğlu; Sedanur Çetin (Buildings)
This study investigated the historical Kabasakal Mosque minaret’s seismic performance in the Şahinbey district of Gaziantep province. After the 6 February 2023 Kahramanmaraş earthquake, the cone and honeycomb sections of the minaret were damaged. The minaret is a typical masonry structure with a cylindrical body and open balconies belonging to the Ottoman period, and the damage that occurred primarily in the weak areas, such as the honeycomb and the cone, caused serious structural problems due to the earthquakes. In the study, a finite element model (FEM) of the minaret was created. Nonlinear time-history analyses were performed using earthquake records recorded in the district where the minaret is located in the finite element model. First, the original state of the minaret (OM model) was analyzed, and its collapse mechanisms were investigated. Then, a proposal was developed to strengthen the minaret’s honeycomb and cone sections with steel rings. This reinforcement was tested with numerical analyses, and the dynamic performances of both the original and reinforcement models were compared. The durability and seismic performance of local materials commonly used in regional structures, such as Urfa stone, were evaluated. It was observed that the proposed reinforcement method reduced the displacement demands in critical areas and increased the overall rigidity of the structure. The study emphasizes the importance of reinforcement methods in protecting historical structures and reveals the proposed solution’s applicability to similar structures.